THE INFLUENCE OF THE EXERCISE PROGRAMS ON THE BOY’S SELFCONCEPT - Dao Chanh Thuc; Nguyen Minh Cuong; Ta Hoang Thien (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This study is to investigate the effectiveness of an exercise program for children from 10 to 11 years old. In this study, 30 subjects were divided into two groups of equal control and training. After completing the procedure, the participants in the training group performed the gymnastics training program for 12 weeks and the control group did nothing. Data collection tool is a demographic questionnaire and a scale of self-concept Piers-Harris. Kolmogorov-Smirnov test is used to test the normal distribution of samples. The research results show that in the training group, the size of the concept of self and the general self concept of children before and after exercise instrument increased significantly. The results also show that the size of happiness and satisfaction of children, both in the control group and in the training group, is significantly different. The study, concluded that a training program in the field of gymnastics training has significantly increased the level of self-concept of children.